SUPERFICIAL CERVICAL PLEXUS BLOCK - Puspadisari, Komang Mega (E-Jurnal Medika Udayana; vol 3 no 1 (2014):e-jurnal medika udayana)
Superficial cervical plexus block is one of the regional anesthesia in  neck were limited to the superficial fascia. Anesthesia is used to relieve pain caused either during or after the surgery is completed. This technique can be done by landmark or with ultrasound guiding. The midpoint of posterior border of the Sternocleidomastoid was identified and the prosedure done on that place or on the level of cartilage cricoid.
Keywords: Regional anestheia, Cervical plexus block, Superficial cervical plexus block